2014
DOI: 10.1039/c3nr06199j
|View full text |Cite
|
Sign up to set email alerts
|

Spin density waves in periodically strained graphene nanoribbons

Abstract: Zigzag graphene nanoribbons (ZGNRs) are antiferromagnetic in the ground state with zero net magnetization due to the compensation of contributions from opposite edges. Uniform deformations (both shear and axial) do not produce magnetization due to symmetry restrictions. However, we report the results of first-principles calculations that predict the induction of spin density waves (SDWs) in ZGNRs under non-uniform periodic strain. Using the density functional theory (DFT) method, we show that a sinusoidal magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The investigation is limited to the model system and simple excitation modes; the spin polarization distribution has seldom been seen. We also notice that someone proposed that there exist spin density waves in the periodically strained GNR by the first principle calculations [22]. On the experiment aspect, G.Z.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The investigation is limited to the model system and simple excitation modes; the spin polarization distribution has seldom been seen. We also notice that someone proposed that there exist spin density waves in the periodically strained GNR by the first principle calculations [22]. On the experiment aspect, G.Z.…”
Section: Introductionmentioning
confidence: 64%
“…Recently Hagymasi et al use the density-matrix renormalization-group algorithm to study some excitations in zigzag GNR [23]. We also notice that some spin density wave (SDW) has been proposed in a zigzag GNR, which is induced by a periodically shear strain on the GNR [24].…”
Section: Introductionmentioning
confidence: 84%
“…In addition, the spin polarized first principle calculations have shown that zigzag GNRs are magnetic in nature, whereas armchair GNRs show non-magnetic behaviour [54]. When the strain is applied to the magnetic GNRs, magnetic moment is induced along zigzag edges with sinusoidal deformations [55].…”
Section: Introductionmentioning
confidence: 99%
“…In principle, by suitable engineering of local strain profiles, all-graphene electronics can be integrated on a single graphene sheet. The various ways to apply inplane strain in graphene nanoribbons (GNRs) including tensile strain [1,2], bending [3,4], and intrinsic rippling [5] can be used to develop materials with tunable properties. Nevertheless, the off-plane, for example, twisting [6], can offer another way to exploit the core and edge region interaction of GNRs.…”
Section: Introductionmentioning
confidence: 99%